2021
DOI: 10.3390/gels7020035
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Thermal Renders with Lightweight and Thermal Insulating Aggregates: Regranulated Expanded Cork, Silica Aerogel and Expanded Polystyrene

Abstract: Following the trend of energy-efficient construction, renders with thermal insulation properties have been studied for replacing conventional renders. However, there are still few studies on the durability of these renders that may become a barrier for their implementation. In this study, the performance of lightweight renders for thermal insulation to accelerated aging cycles and freeze/thaw cycles is discussed. For this purpose, renders with regranulated expanded cork (GEC), silica aerogel (SA), and expanded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Recent publications suggest also that the enhancement of the mechanical parameters with retained insulating properties might be achieved by adding other lightweight aggregates along with the aerogel [ 76 , 87 , 90 , 94 , 95 , 96 , 97 , 98 ]. Aggregates used in these solutions include expanded cork, expanded polystyrene, expanded glass or expanded perlite and vermiculite.…”
Section: Composition Mechanical and Insulating Properties Of Cementit...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent publications suggest also that the enhancement of the mechanical parameters with retained insulating properties might be achieved by adding other lightweight aggregates along with the aerogel [ 76 , 87 , 90 , 94 , 95 , 96 , 97 , 98 ]. Aggregates used in these solutions include expanded cork, expanded polystyrene, expanded glass or expanded perlite and vermiculite.…”
Section: Composition Mechanical and Insulating Properties Of Cementit...mentioning
confidence: 99%
“…Aggregates used in these solutions include expanded cork, expanded polystyrene, expanded glass or expanded perlite and vermiculite. For example, Morgado et al used regranulated expanded cork, silica aerogel and expanded polystyrene as aggregates for energy-efficient building façades [ 87 ]. They indicated that, in doing so, the weight of the samples was decreased, whereas the compression strength was slightly increased.…”
Section: Composition Mechanical and Insulating Properties Of Cementit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Aerogels, miracle materials for the 21st century, are considered to be promising and useful because of their ultralow density (0.003–0.1 g/cm 3 ), high porosity (80–99.8%), low thermal conductivity (0.013–0.14 W/m·K), high specific surface area (500–1200 m 2 /g), low dielectric constant ( k = 1.0–2.0), and high acoustic impedance (~1.05 MRayl) [ 1 , 2 , 3 ]. Because of these excellent properties, aerogel materials have recently been the focus of considerable research and have been used in a wide range of applications such as thermal insulation [ 4 , 5 , 6 ], acoustic insulation [ 7 ], adsorption [ 8 , 9 ], flexible energy storage devices [ 10 ], and drug and catalyst carriers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%